A Combined Site‐Specific Metals Sorption and Transport Model for Intact Soil Columns. Issue 4 (4th October 2013) - Serrano, Susana; Vlassopoulos, Dimitri; Garrido, Fernando; O'Day, Peggy A.
Abstract : Simulation of metal attenuation in natural soil environments requires model descriptions of combined sorption and transport processes that are generally transferable to assess potential risk. A non‐electrostatic equilibrium ion exchange and surface complexation model (SCM), developed from batch experiments of Pb and Cd sorption to natural soils, was used to describe coupled transport in undisturbed soil column experiments. The model, based on soil mineral component additivity, was applied to reproduce metal transport without adjustment of sorption reactions or conditional equilibrium constants derived from batch experiments. Good agreement between model results and experimental soil column data for Pb and Cd uptake and release indicates that their transport at two different concentrations and flow rates can be described by sorption equilibria except for Pb at low concentration and slow flow rate. Model simulations were less successful in describing the transport behavior of Ca and Al, and effluent acidic pH, suggesting that additional reactions involving Al are needed. Fluctuations in effluent pH were not well simulated by the model, but model results were within ∼0.25 to 0.5 log units of observed pH. Model results suggest that sorption competition between Pb, Cd, and Ca (from the background electrolyte) was mostly associated with ion exchange sites attributed to weathered illite at acidic pH, with additional adsorption of Pb on hydroxyl sites of extractable Fe‐oxides. Simulations predicted net retention of Pb and Cd by soil columns from −9% to +13% of observed metal retention. This study demonstrates the ability to transfer a relatively small set of equilibrium sorption reactions and constants from batch to hydrodynamic column experiments under a limited set of flow conditions without arbitrary parameter fitting by using soil properties and mineralogy as constraints in model formulation.